STUDYING IMMUNOBIOLOGICAL CHARACTERISTICS OF FMDV TYPE O ISOLATES RECOVERED IN THE SOUTH KOREA - A. A. Funtikov; S. R. Kremenchugskaya; T. K. Mayorova; S. N. Fomina; D. A. Lozovoy; V. M. Zaharov (Ветеринария сегодня)
The paper presents the results of adaptation of FMDV Type O isolates obtained from the Animal and Plant Quarantine Agency to pig cell cultures and organisms as well as studies of their infectivity, antigenic activity as well as stability during passages in the PSGK continuous cell culture. Antigenic matching of FMDV Type O isolates, 2014-2015, obtained from the Animal and Plant Quarantine Agency of the Republic of Korea, with Russian and foreign FMDV Type O production strains was studied. Special attention was given to determination of the inoculation dose for virus cultivation in PSGK-30 for the purpose of subsequent preparation of antigenic preparations and FMD vaccines. The results of strain studies served a basis for their depositing into the FGBI “ARRIAH” strain collection.